PENGARUH CURRENT RATIO (CR) DAN DEBT TO EQUITY RATIO (DER) TERHADAP RETURN ON ASSETS (ROA) PADA PT. UNILEVER INDONESIA TBK - Nurwita, Nurwita; Lisdawati, Lisdawati (Indonesian Journal of Economy, Business, Entrepreneuship and Finance, 2025)
This study aims to determine the partial and simultaneous effect between Current Ratio and Debt to Equity Ratio on Return on Assets at PT. Unilever Indonesia Tbk Period 2014-2023. The method used in this study is a quantitative method using secondary data in the form of financial statements of PT. Unilever Indonesia Tbk Period 2014-2023. With descriptive statistical analysis methods, classical assumption tests and multiple linear analysis. Furthermore, hypothesis testing uses the F-test, T-test, Correlation Coefficient and Determination Coefficient assisted by SPSS 26. Based on the results of the T- test research, Current Ratio has no effect on Return on Assets. Debt to Equity Ratio has a negative but significant effect on Return on Assets. Then based on the results of the F-test, Current Ratio and Debt to Equity Ratio simultaneously have an effect on Return on Assets. Meanwhile, based on the determination coefficient, Current Ratio and Debt to Equity Ratio have an effect on Return on Assets